High-resolution mapping reveals a Ht3-like locus against northern corn leaf blight - Zhu, Mang; Ma, Jun; Liu, Xinfang; Guo, Yanling; Qi, Xin; Gong, Xue; Zhu, Yanbin; Wang, Yanbo; Jiang, Min (Frontiers in Plant Science, 2022)
Northern corn leaf blight (NCLB), caused by the fungal pathogen Exserohilum turcicum, poses a grave threat to maize production worldwide. The resistance gene in A619Ht3, discovered decades ago, is an important genetic resource for NCLB control. By using a pair of near-isogenic lines (NILs) A619Ht3 and A619, together with the resistant and susceptible bulks derived from the cross of A619Ht3 and L3162 lines, we initially detected a Ht3-like (Ht3L) locus in bin 8.06 that was closely associated with NCLB resistance. We then performed five rounds of fine-mapping, which ultimately delimited the Ht3L locus to a 577-kb interval flanked by SNP markers KA002081 and KA002084. Plants homozygous for the Ht3L/Ht3L genotype exhibited an average reduction in diseased leaf area (DLA) by 16.5% compared to plants lacking Ht3L locus. The Ht3L locus showed extensive variation in genomic architecture among different maize lines and did not appear to contain any genes encoding canonical cell wall-associated kinases against NCLB. Moreover, the Ht3L locus was located ∼2.7 Mb away from the known Htn1 locus. We speculate that the Ht3L locus may contain a bona fide Ht3 gene or a novel NCLB resistance gene closely linked to Ht3. In practice, the Ht3L locus is a valuable resource for improving maize resistance to NCLB.